2019
DOI: 10.1007/s11357-019-00110-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous congestion promotes blood-brain barrier disruption and neuroinflammation, impairing cognitive function in mice

Abstract: Cognitive impairment is one of the most common co-occurring chronic conditions among elderly heart failure patients (incidence: up to~80%); however, the underlying mechanisms are not completely understood. It is hypothesized that in addition to decreased cardiac output, increases in central-and consequentially, cerebral-venous pressure (backward failure) also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 97 publications
0
35
0
Order By: Relevance
“…Burns have been shown to induce cognitive impairment and abnormal behavior (4,(8)(9)(10)(11)(12). Given the fact that BBB dysfunction is the key factor in cognitive impairment (50)(51)(52)(53)(54)(55)(56)(57) and that MSCs can effectively improve the integrity of BBB, we investigated whether burns could induce BBB dysfunction and neuroinflammation as well as evaluated its potential mechanism and the best time point for intervention to improve these effects after burn.…”
Section: Discussionmentioning
confidence: 99%
“…Burns have been shown to induce cognitive impairment and abnormal behavior (4,(8)(9)(10)(11)(12). Given the fact that BBB dysfunction is the key factor in cognitive impairment (50)(51)(52)(53)(54)(55)(56)(57) and that MSCs can effectively improve the integrity of BBB, we investigated whether burns could induce BBB dysfunction and neuroinflammation as well as evaluated its potential mechanism and the best time point for intervention to improve these effects after burn.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ICPs in IIH and MS appear to be on a continuum. In a mouse model of IIH, cerebral venous congestion per se was found to cause BBB disruption and neuro-inflammation (Fulop et al, 2019) similar to the earliest manifestations of an MS plaque (Wuerfel et al, 2004).…”
Section: Are Ms and Idiopathic Intracranial Hypertension Related?mentioning
confidence: 97%
“…For example, Huh et al (2008) showed that BBB disruption in their midline CCI rat model of mTBI occurs within 6 h after impact, while glial fibrillary acidic protein (GFAP) immunoreactivity in the cortex at 24 h was comparable to that observed in sham-injured animals, and astrogliosis was only observed on day 3 and day 8 post-injury. As BBB breakdown and extravasation of plasma proteins such as fibrinogen are a driving force of microglia activation after injury ( Davalos et al, 2012 ) and capable of inducing neurotoxic reactive astrocytes after TBI ( Liddelow and Barres, 2017 ; Liddelow et al, 2017 ) and cognitive impairment ( Fulop et al, 2019 ), the vascular link between mTBI and neuroinflammation should be defined in future studies.…”
Section: Blood–brain Barrier Dysfunction and Neuroinflammation In Milmentioning
confidence: 99%